Efficient extraction of copper and zinc from seafloor massive sulphide rock samples from the Loki's Castle area at the Arctic Mid-Ocean Ridge. (January 2018) - Kowalczuk, Przemyslaw B.; Snook, Ben; Kleiv, Rolf Arne; Aasly, Kurt
Graphical abstract: Highlights: Loki's Castle at the Arctic Mid-Ocean Ridge is a potential marine metal resource. Nitric acid can be used to extract metals from seafloor massive sulphides (SMS) Copper and zinc can be successfully recovered during nitric acid leaching. Extraction of copper and zinc is controlled by temperature and acid concentration. An extraction efficiency plateau is reached well within 'normal' operating limits. Abstract: Seafloor massive sulphide (SMS) deposits have been identified as important marine metal resources for the future. However, literature on the recovery/extraction of metals from SMS is currently limited, and to date, no research has been published on the processing of SMS from the active hydrothermal vent field at the Arctic Mid-Ocean Ridge. In this paper extraction of copper and zinc, as economically important metals, from the seafloor massive sulphide rock samples from the Loki's Castle area at the Arctic Mid-Ocean Ridge was investigated during nitric acid leaching. The results presented are of the various leaching experiments conducted under different conditions to optimise the extraction of copper and zinc. The mineralogical analysis indicated that the main copper and zinc bearing minerals were chalcopyrite and sphalerite, respectively. It was shown that the leaching efficiency and extraction of copper and zinc can be controlled mainly by temperature and acid concentration. The elemental composition and mineralogical data indicated that 95% of copper and zinc bearing minerals were leached out after 3 h, at the solid-to-liquid ratio of 1:10, temperature of 90 °C and acid concentration of 10%.